Metabolic and nutritional effects of vitamin A on growth, lipid metabolism, antioxidant capacity and hepatopancreas health of juvenile mud crab (Scylla paramamosain) - Zheng Tang; Shichao Xie; Yao Deng; Wenhao Zhan; Hongyu Peng; Yinqiu Tian; Haiqing Cao; Min Jin; Binjie Zhou; Yushan Zou; Juntao Gu; Peng Sun; et al. (Aquaculture Reports)
An 8-week feeding trial was conducted to determine the effects of different vitamin A (VA) level on growth performance, lipid metabolism, antioxidant capacity and hepatopancreas health of juvenile mud crab (Scylla paramamosain). Six experimental diets with different VA level were created, and the actual VA analysis values were 0.00, 2.52, 5.40, 11.59, 18.68 and 38.18 mg/kg, respectively. A total of 180 disease-free crabs weighing 15.03 ± 0.01 g were randomly transferred to 180 independent baskets, each treatment consisting of 3 replicates, with 10 crabs in each replicate. The results indicated that dietary 5.40 mg/kg VA significantly improved the FW, PWG, SGR and MR of juvenile mud crab. Crabs fed diet containing 5.40 mg/kg VA exhibited the highest concentrations of T-CHO, HDL-C and LDL-C and the activity of T-AOC in hemolymph, the activities of GSH-PX and T-SOD in hepatopancreas, and the expressions of fatp4, cptⅠ, Δ6 fad and elovl6 in hepatopancreas were significantly up-regulated, while the hepatopancreas MDA concentration was the lowest (P < 0.05). Besides, dietary 38.18 mg/kg VA up-regulated the expressions of relish, rab6a and bax, while significantly down-regulated the expressions of alf-3 and bcl-2. The correlation analysis results showed that fatp4 and gpx both have a significant positive correlation with growth performance related parameters, suggesting they may be crucial for VA's physiological functions. In conclusion, the broken-line equations of PWG relative to the dietary VA level indicated that the optimal dietary VA requirement for juvenile mud crab was established as 2.96 mg/kg. Dietary 5.40 mg/kg VA could improve the growth performance, lipid metabolism and antioxidant capacity of juvenile mud crab, meanwhile avoid hepatopancreas damage, inflammatory response and apoptosis caused by excessive VA.